(untitled) (Journal of Fiber Bioengineering and Informatics, 2010)
This paper evaluates and compares the electromagnetic (EM) shielding characteristics of a diverse range of conductive fabrics in order to analyse their suitability for use in wearable medical applications. The Shielding Effectiveness (SE) was characterised in terms of fabric structures, conductive materials, mass, thickness and washing durability. Experiments were carried out on single and double layers of fabrics using broad frequency range and SE was measured using different methodologies. EM shielding is the process of limiting the flow of EM fields between two locations by a barrier. The shielding barrier needs to have high conductivity, dielectric constant or high magnetic permeability, and the shielding happens due to reflection, absorption or multiple reflections of the incident radiation by the barrier. Therefore, shielding is important to block electromagnetic radiation that could be harmful to electronic devices, environment and humans.